Neuropeptide Systems as Targets for Parasite and Pest Control - Geary, Timothy G.; Maule, Aaron G. (Advances in Experimental Medicine and Biology, 2010)
This book was assembled to focus attention on this promising field by compiling a comprehensive review of recent research on neuropeptides in arthropods and helminths, with contributions from many of the leading laboratories working on these systems. The organization of the chapters is intended to provide an overview of the organism-level biology of neuropeptidergic function in insects and helminths, progressing to an understanding of the molecular biology of the genes that encode their precursors and receptors in these organisms. We include for perspective consideration of the state of the art in discovery of insecticides and anthelmintics, a review of drugs that affect similar systems in nematodes, and a summary of drug discovery efforts that target mammalian neuropeptide receptors for therapy of non-infectious diseases in humans.